Website Satisfaction Analysis Using Usability Scale System In Cilongok District Office - Bergas Pamungkas; Didi Supriyadi; Sarah Astiti (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
Abstract Indonesia is a country with a number of governmental areas where there are 416 districts, 98 cities, 7,094 sub-districts, 8,490 sub-districts, and 74,957 villages in Indonesia. website-based, but there are still problems with the satisfaction of the services used by users or the community. Basically, all website-based information services must be in tune with the needs of what users will do on the website, so from this problem the researcher proposes a solution to creating website-based information services according to user requests both in terms of user interface and user experience. In the existing problem, the researcher uses the system usability scale (SUS) method to find out the points that must be corrected for the convenience of using information services in Cilongok district. The SUS method is very suitable for measuring the satisfaction level of users of information-based services in Cilongok sub-district so that users feel satisfied, feel that the information is very clear and make the community more familiar with website-based information technology. Keywords: Website, Satisfaction Level and System Usability Scale (SUS)